Standards System for High-Quality Development of Ecological Civilization: Problems and Implementation Path - Cai Wenbo (《中国工程科学》杂志社, 2021)
The ecological civilization construction in China currently demands high-quality development, and a standards system can guide and support the high-quality development of ecological civilization. In this study, we review the strategic demand for the high-quality development of ecological civilization, present the theoretical and practical progress of the standards system, and summarize the problems regarding the construction of the current standards system, such as lack of standards in key areas and a low implementation rate. Moreover, we propose several suggestions for optimizing the framework and content of the standard system and implementation paths for key areas. Specifically, a standards system for realizing ecological product values should be established to support the development of ecological economy; the standards system for ecological and environmental quality should be improved to guarantee national ecological and environmental safety; terrestrial and marine standards systems should be promoted to support territory spatial arrangement; and a green living standards system should be established to regulate the ecological culture construction.